Acts and texts : performance and ritual in the Middle Ages and the Renaissance - Postlewate, Laurie, 1957-; Hüsken, Wim N. M. (Ludus, 2007)
For the Middle Ages and Renaissance, meaning and power were created and propagated through public performance. Processions, coronations, speeches, trials, and executions are all types of public performance that were both acts and texts: acts that originated in the texts that gave them their ideological grounding; texts that bring to us today a trace of their actual performance. Literature, as well, was for the pre-modern public a type of performance: throughout the medieval and early modern periods we see a constant tension and negotiation between the oral/aural delivery of the literary work a.